Mississippian Effigy Pipes and the Glendon Limestone. Issue 2 (20th April 2011) - Steponaitis, Vincas P.; Dockery, David T.
Abstract : Large effigy pipes made of limestone are found at Mississippian sites across much of the American South. Here we examine a sample of these pipes with the goal of identifying their geological sources, which are inferred from the fossils visible in the rock. All but one of the pipes in our sample are made of Glendon limestone, a distinctive material that outcrops most abundantly near Vicksburg, Mississippi. Based on the geological and distributional evidence, we argue that these Glendon limestone pipes were crafted in the Lower Mississippi Valley. Our study also demonstrates the efficacy of using fossils as a nondestructive way of determining the provenance of limestone artifacts.